VARIABLE THERMOPHYSICAL PROPERTY AND OHMIC HEATING IMPACT ON RADIATIVE CASSON FLUID FLOW PAST A STRETCHING CYLINDER - Oladoja, Adebayo Stephen; Samuel, Damilare John; Chukkol, Yusuf Buba (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates the effect of variable thermophysical properties on radiative Casson fluid flow around a stretching cylinder. The governing partial differential equations for momentum and energy are changed into ordinary differential equations with suitable similarity transformations. Our mathematical model analyses the impact of variable thermal conductivity, viscosity, and radiation parameters on the fluid flow system. The resulting coupled nonlinear equations are solved numerically using the Runge-Kutta fourth-order method with shooting technique. The effect of key parameters including Casson fluid parameter, thermal radiation parameter, magnetic parameter, Grashof number, Prandtl number, Eckert number, ohmic heating parameter and Biot number on velocity and temperature profiles is examined. Results indicate that increasing the Casson parameter reduces fluid velocity while increasing the temperature distribution. The thermal boundary layer thickness is seriously affected by the radiation parameter and variable thermal conductivity. In addition, the study reveals that heat transfer rates at the surface increase with higher values of the Biot number. These findings provide valuable insights into heat transfer optimization in industrial applications involving non-Newtonian fluids with radiative effects and variable properties.